Ration Evaluation for In Vitro Digestibility Application Using Cattle and Buffalo Faeces as Inoculum - Sudirman (Sudirman); R. Utomo; Z. Bachruddin; B. P. Widyobroto; Dahlanuddin (Dahlanuddin) (Faculty of Animal Science, Universitas Gadjah Mada, 2006)
File lengkap ada dalam bentuk PDF dibawah ini